2022
DOI: 10.1177/01945998221083845
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID‐19 Pandemic on Otolaryngology Trainee Surgical Case Numbers: A Multi‐institutional Review

Abstract: Objective To determine the effect of the initiation of COVID-19–related restrictions on the volume of surgical cases performed by otolaryngology trainees. Study Design Multi-institutional retrospective analysis of resident surgical case logs. Setting Accredited residency training programs in otolaryngology head and neck surgery. Methods Resident surgical case logs were combined from 6 residency training programs from different regions of the United States. Case volumes were compared between the calendar year b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This is similar to stable case volumes noted in trainee case logs including urology residents, Society of Urologic Oncology fellows, and general surgery residents 10–12 . However, for some surgical specialties, there were significant decreases in volume including ophthalmology and otolaryngology 13,14 . This may reflect differences in the proportion of elective cases as well as the relative risk of COVID‐19 transmission during the procedures.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This is similar to stable case volumes noted in trainee case logs including urology residents, Society of Urologic Oncology fellows, and general surgery residents 10–12 . However, for some surgical specialties, there were significant decreases in volume including ophthalmology and otolaryngology 13,14 . This may reflect differences in the proportion of elective cases as well as the relative risk of COVID‐19 transmission during the procedures.…”
Section: Discussionsupporting
confidence: 62%
“…[10][11][12] However, for some surgical specialties, there were significant decreases in volume including ophthalmology and otolaryngology. 13,14 This may reflect differences in the proportion of elective cases as well as the relative risk of COVID-19 transmission during the procedures. For urology FPMRS fellows, there was a statistically significant decrease among two COVID-affected cohorts: GI procedures decreased for AY 2020−2021 from AY 2019−2020 (4.2 vs. 8.9, p = 0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Case reduction and surgical skill perceived by both residents and staffs were similar to previous studies that measure the case numbers reduction, 17 , 18 and also similar to the previous study that revealed a significant decrease in surgical case volumes. 19 The hospital’s policy of reducing surgical cases might cause their lack of confidence. The more difficult and complicated the procedures were, the more the residents felt unconfident ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The postponement and cessation of elective surgeries caused by the COVID-19 pandemic resulted in a significant reduction in operative volume for residency programs. 7,[10][11][12][13] In a survey study of head and neck program directors in the US, 70% (26/37) reported 50% to 90% reduction in elective cases performed by fellows and significant curtailing of didactics in March and April of 2020. 14 Izreig et al determined that the surgical volume across all subspecialties except head and neck cancer surgeries experienced higher rates of procedure cancellations leading to reduction in performed cases in 2020 compared to 2019.…”
Section: Introductionmentioning
confidence: 99%
“…5 These changes may have lasting repercussions such as substantial surgical backlog, 16 financial losses of up to $323 billion in 2020 projected by the American Hospital Association, 17 and perhaps most strikingly, decreased surgical case experience among trainees. 7,[10][11][12][13] We sought to examine the impact of COVID-19 on otolaryngology surgical training through and after the height of the pandemic by examining key indicator case trends in an academic tertiary care center.…”
Section: Introductionmentioning
confidence: 99%